2017
DOI: 10.3390/metabo7030038
|View full text |Cite
|
Sign up to set email alerts
|

Non-Targeted Metabolomics Analysis of Golden Retriever Muscular Dystrophy-Affected Muscles Reveals Alterations in Arginine and Proline Metabolism, and Elevations in Glutamic and Oleic Acid In Vivo

Abstract: Background: Like Duchenne muscular dystrophy (DMD), the Golden Retriever Muscular Dystrophy (GRMD) dog model of DMD is characterized by muscle necrosis, progressive paralysis, and pseudohypertrophy in specific skeletal muscles. This severe GRMD phenotype includes moderate atrophy of the biceps femoris (BF) as compared to unaffected normal dogs, while the long digital extensor (LDE), which functions to flex the tibiotarsal joint and serves as a digital extensor, undergoes the most pronounced atrophy. A recent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 62 publications
(76 reference statements)
0
15
0
Order By: Relevance
“…A recent study on muscle metabolomics of a dog model for Duchenne muscular dystrophy reported arginine and proline metabolism as the top changed pathways (Abdullah et al , ), which is also the top pathway in the blood metabolomes of our NMD patients. These findings suggest that the blood metabolomic responses to muscular dystrophy are conserved in species and that a semiquantitative metabolomics assay—or arginine/proline content of serum—could be useful as a multi‐biomarker for treatment follow‐up in muscle dystrophies.…”
Section: Discussionmentioning
confidence: 72%
“…A recent study on muscle metabolomics of a dog model for Duchenne muscular dystrophy reported arginine and proline metabolism as the top changed pathways (Abdullah et al , ), which is also the top pathway in the blood metabolomes of our NMD patients. These findings suggest that the blood metabolomic responses to muscular dystrophy are conserved in species and that a semiquantitative metabolomics assay—or arginine/proline content of serum—could be useful as a multi‐biomarker for treatment follow‐up in muscle dystrophies.…”
Section: Discussionmentioning
confidence: 72%
“…Carnosine acts as an antioxidant and reduces free radicals generated from excess lipid and sugar oxidation 36 . Untargeted metabolomic analysis of skeletal muscle revealed lower concentrations of carnosine in a dystrophin deficient canine model compared to healthy controls that might explain the oxidative stress that is associated with DMD 37 . The significance of lower concentrations of circulating CNDP1 in GC-naïve DMD patients that increased following GC treatment at levels exceeding that in the controls is not well understood.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, Willis and his colleagues reported that altered lipid metabolism genes were relative with arginine and proline metabolism. [22] But, the precise mechanism about the dysfunctional arginine metabolism still remains unknown and deserve to be further studied.…”
Section: Discussionmentioning
confidence: 99%